Analysis of Maturity Level Concerning Alignment of Information Technology Strategy and Business Strategy Using Luftman Model - Junidar Junidar; Kikye Martiwi Sukiakhy; Dwi Mardiana (Green Publisher Indonesia, 2023)
Alignment of business strategy and IT organization is the key to realizing IT benefits for businesses. The gap between the IT strategy and the business strategy will have an impact on the organization's business performance, especially if the organization relies on IT in its business operations or makes IT one of its selling points. Raden Fatah Palembang State Islamic University as one of the institutions of college sees IT as a mandatory requirement to build competence and capability in the framework of competition in its area. Based on these requirements, the alignment of business and IT strategy is aligned with Raden Fatah Palembang State Islamic University using the Luftman SAMM (Strategic Alignment Maturity Model) model. Currently Raden Fatah Palembang State Islamic University has a value of alignment strategy that is in level 4 (Initial), where at that level, the alignment strategy is still missing or not implemented.